Confiyou : Aplikasi Pelatihan Presentasi & Negosiasi Berbasis Vr Untuk SDM UMKM - Kamil Athallah, Aufa; Noor Prawita, Fat’hah (eProceedings of Applied Science, 2023)
MSME entrepreneurs (Micro, Small and Medium Enterprises) have a product that continues to grow and is well known not only in remote parts of the country, but also in foreign countries. Because the products they have have a high enough appeal, many requests and orders are received from foreign countries. It is undeniable that some of these MSME entrepreneurs have difficulty in introducing and presenting their products, due to difficulties or lack of skill in using foreign languages, especially English. The ConfiYou application is a VR-based android application that aims to train users' English skills. In this application there will be 2 menu options, such as presentation & negotiation, later the user will present and introduce the product or business they have using Powerpoint. After making a presentation, there will be an audience who asks and the user will answer the question. After that has been passed, the training simulation will be completed and the results of the training simulation carried out by the user will appear. ConfiYou application development will continue with the hope of adding the required features and maximizing existing features, testing the ConfiYou application will be carried out by users, namely MSME HR to find out how to use the ConfiYou application, of course assisted by presentation materials, negotiation, product introduction, and English language skills in the form of videos and powerpoint slides.Keywords: MSME, Presentation, Negotiation, Product